The prevalence of victimization and the internet abuse in student population - Baltezarević Vesna; Baltezarević Radoslav; Baltezarević Borivoje (Temida)
The use of modern information technology has contributed to the creation of new media and virtual tools that contribute to mass social interaction. The Internet has enabled networking communicator, associating in virtual communities and the creation of parallel communication space. However, despite all the good things they bring with them, new technologies are leading to the emergence of various forms of victimization in the virtual space. The ability to communicate anonymously or through a fictitious identity on the new media platforms created a favorable climate for the operation of the “dark side” of the Internet. Violence on the Internet, known as the cyberbullying is becoming a topic for many researchers mainly focusing on research and description of the phenomenon in adolescent population. The paper aims to examine the theoretical aspects of cyberbullying and to present the existing research, as well as the results of the pilot research work on the social networks behavior of final year students of the Faculty of Culture and Media, conducted by the authors. The paper shows that violence on the Internet exists in this part of the student population.